2021
DOI: 10.3390/su132112245
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Masonry Mortars with Fly Ash, Blast Furnace Granulated Slag and Wheat Straw Ash

Abstract: Due to greenhouse gas emissions, the production of cement clinker is considered unsustainable and many attempts are being made to replace cement with alternative materials sourced from agriculture, industry and other urban practices, such as construction and demolition works. The aim of this paper is to analyze the effects of cement substitution by locally available waste materials in Serbia, such as fly ash (FA), blast furnace granulated slag (BFGS) and wheat straw ash (WSA), up to the 50% replacement volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The results indicate that up to 40% of cement could be replaced to obtain the requisite compressive strength of masonry mortar. Similar recommendations were given by Šupić et al [6], whereas research findings highlight the possibility of replacing cement with slag (50%), fly ash (30%) or wheat straw ash (30%) while maintaining its performance and improving the economic and environmental impacts of masonry mortar production. Lertwattanaruk et al [14] developed a masonry mortar based on four types of waste seashells, including short-necked clam, green mussel, oyster, and cockle as cement replacement (5%, 10%, 15%, or 20% by weight).…”
Section: Review On the Application Of Biomass Ashes In Masonry Mortarssupporting
confidence: 74%
See 1 more Smart Citation
“…The results indicate that up to 40% of cement could be replaced to obtain the requisite compressive strength of masonry mortar. Similar recommendations were given by Šupić et al [6], whereas research findings highlight the possibility of replacing cement with slag (50%), fly ash (30%) or wheat straw ash (30%) while maintaining its performance and improving the economic and environmental impacts of masonry mortar production. Lertwattanaruk et al [14] developed a masonry mortar based on four types of waste seashells, including short-necked clam, green mussel, oyster, and cockle as cement replacement (5%, 10%, 15%, or 20% by weight).…”
Section: Review On the Application Of Biomass Ashes In Masonry Mortarssupporting
confidence: 74%
“…Several researchers have introduced agricultural wastes, in form of ash, as a partial replacement of cement or as an alkaline activator including rice husk ash (RHA) [1], olive waste ash (OWA) [2], sugar cane bagasse ash (SCBA) [3], corn cob ash (CCA) [4], palm oil fuel ash (POFA) [5], wheat straw ash (WSA) [6], soya straw ash (SSA) [7], almond shell ash (ASA) [8], cornstalk ash (CSA) [9], barley straw ash (BSA) [10], etc.…”
Section: Review On the Application Of Biomass Ashes In Masonry Mortarsmentioning
confidence: 99%
“…An increase in compressive strength, a simultaneous decrease in the modulus of elasticity, and an increase in water absorbability in comparison with traditional cement mortars were observed. For years, research around the world has covered the use of fly ash and blast furnace slag in cement composites, mainly as a hydraulic additive [43,44] but also in geopolymer concrete [45][46][47][48], where pozzolana is indispensable for the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been attempted by a number of researchers to develop alternative cementitious materials using HRA. Rice husk ash (RHA) [ 5 ], palm oil fuel ash (POFA) [ 6 ], sugar cane bagasse ash (SCBA) [ 7 ], wheat straw ash (WSA) [ 8 ] and corn cob ash (CCA) [ 9 ] are some of the HRA that have evidently been reported for their suitability as pozzolans. The majority of the agricultural biomass resources in Serbia lie in corn biomass, more than 25% in the straw of cereals, and the rest in harvest residues of sunflower, soybean and oilseed rape.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring the possibility of the application of HRA as SCMs in mortar production in Serbia has been recently initiated. Few earlier studies are available on the effect of WSA incorporation on the flexural and compressive strength of blended cement mortar [ 11 ] and masonry mortar [ 8 ]. No studies referring to CCA application in cement-based composites in Serbia can be found, while there have been studies giving an account of this by-product utilization as a SCM in other countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%